Association between classes and subclasses of polyphenol intake and 5‐year body weight changes in the EPIC‐PANACEA study. Issue 4 (24th January 2023) - Castañeda, Jazmin; Gil‐Lespinard, Mercedes; Almanza‐Aguilera, Enrique; Llaha, Fjorida; Gómez, Jesús‐Humberto; Bondonno, Nicola; Tjønneland, Anne; Overvad, Kim; Katzke, Verena; Schulze, Matthias B.; Masala, Giovanna; Agnoli, Claudia; et al.
Abstract: Objective: The aim of this study was to evaluate the associations among the intake of total polyphenols, polyphenol classes, and polyphenol subclasses and body weight change over 5 years. Methods: A total of 349, 165 men and women aged 25 to 70 years were recruited in the Physical Activity, Nutrition, Alcohol, Cessation of Smoking, Eating Out of Home and Obesity (PANACEA) project of the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort from nine European countries. Body weight was measured at baseline and at follow‐up after a median time of 5 years. Polyphenol intake, including four main polyphenol classes and eighteen subclasses, was estimated using validated dietary questionnaires and Phenol‐Explorer. Multilevel mixed linear regression models were used to estimate the associations. Results: Participants gained, on average, 2.6 kg (±5.0 kg) over 5 years. Total flavonoids intake was inversely associated with body weight change (−0.195 kg/5 years, 95% CI: −0.262 to −0.128). However, the intake of total polyphenols (0.205 kg/5 years, 95% CI: 0.138 to 0.272) and intake of hydroxycinnamic acids (0.324 kg/5 years, 95% CI: 0.267 to 0.381) were positively associated with body weight gain. In analyses stratified by coffee consumption, hydroxycinnamic acid intake was positively associated with body weight gain in coffee consumers (0.379 kg/5 years, 95% CI: 0.319 to 0.440), but not in coffee nonconsumers (−0.179 kg/5 years, 95% CI: −0.490 to 0.133). Conclusions: Higher intakes of flavonoids and their subclasses are inversely associated with a modest body weight change. Results regarding hydroxycinnamic acids in coffee consumers require further investigation.